Performance Evaluation of a Modified Granulator Based on Operating Parameters for Bioherbicide Granule Production - Gatot Pramuhadi; Muhamad Achmad Chozin; Endang Gunawan; Vitho Alveno; Kusuma Darma (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Bioherbicide granules is a new innovation in weed control produced using a granulator machine. This study aimed to evaluate the performance of a modified pan granulator prototype intended for bioherbicide granule production. Wheat flour and tapioca flour were used as starch-based substitute materials to assess the mechanical performance of the granulator. Granulation performance was evaluated by varying the pan inclination angle, pan rotational speed, and spraying duration. The experimental treatments consisted of two inclination angles (40° and 45°), two rotational speeds (15 rpm and 35 rpm), and three spraying durations (20 s, 30 s, and 40 s). The results showed that the machine produced granules with an average diameter ranging from 4.01 mm to 6.08 mm and diameter uniformity between 90.80% and 96.23%. Increasing the spraying duration enhanced inter-particle bonding, resulting in larger granule diameters, while increasing the pan rotational speed from 15 rpm to 35 rpm reduced granule size due to stronger material–scraper interactions. The most favorable granulation performance among the tested conditions was obtained at pan inclination angle of 40° and rotational speed of 35 rpm, producing average granule diameters <5 mm that in accordance with SNI 7698:2011. Higher rpm resulted in more stable granule diameter uniformity, indicating improved particle homogeneity.